Beyond human rights and the war on terror - Juss, Satvinder S. (Satvinder Singh) (London : Routledge, 2019)
This edited collection provides a comprehensive, insightful, and detailed study of a vital area of public policy debate as it is currently occurring in countries across the world from India to South Africa and the United Kingdom to Australia. Bringing together academics and experts from a variety of jurisdictions, it reflects upon the impact on human rights of the application of more than a decade of the "War on Terror" as enunciated soon after 9/11. The volume identifies and critically examines the principal and enduring resonances of the concept of the "War on Terror". The examination covers not only the obvious impacts but also the more insidious and enduring changes within domestic laws. The rationale for this collection is therefore not just to plot how the "War on Terror" has operated within the folds of the cloak of liberal democracy, but how they render that cloak ragged, especially in the sight of those sections of society who pay the heaviest price in terms of their human rights. This book engages with the public policy strand of the last decade that has arguably most shaped perceptions of human rights and engendered debates about their worth and meaning. It will be of interest to researchers, academics, practitioners, and students in the fields of human rights law, criminal justice, criminology, politics, and international studies.
Foreword / Manfred Nowak -- Assessing unconventional applications of the 'terrorism' label / Sudha Setty -- Separatist, not terrorist : case studies from Southeast Asia / Nadirsyah Hosen -- The 'refugee warrior' in an age of revolutionary violence / Satvinder S. Juss and Jeni Mitchell -- The ISIL jihadists of Saudi Arabia / Abdullah K. Al-Saud -- The criminal law implications of the 'war on terror' & the status of foreign fighters : a Swiss perspective / Roberta Arnold -- Disrupting terrorist activity : what are the limits to criminal methods of disruption? / Stuart Macdonald and Lord Carlile -- The evolving common law jurisprudence combatting the threat of terrorism in Canada / James Simeon -- Human rights & anti-terror laws in Australia / George Williams -- The legacy of apartheid and South Africa's struggle to contain contemporary form of terrorism and violent extremism / Martin Ewi and Willem Els -- India and the global war on terror : Indian counterterrorism and the influence of the global war on terror / Harsh V. Pant and Ivan Lidarev.
OCLC-licensed vendor bibliographic record.
Keywords: Terrorism -- Prevention -- Law and legislation; Terrorism (International law); LAW / Administrative Law & Regulatory Practice; LAW / Comparative; LAW / Constitutional; LAW / International